Development Trends in Automation and Metrology. Issue 24 (2015) - Bauer, J.M.; Bas, G.; Durakbasa, N.M.; Kopacek, P.
Abstract: Metrology and Automation are two of the fastest growing latest technological trends. Both disciplines are nowadays and will be in the future more and more influenced by micro-, nano- and femto-technologies. Increasing key drivers of the technological challenges are raised new productivity enhancement requirements with increasing key drivers of the technological challenges For example in production automation we have the new headlines new materials, production 4.0 and in metrology measurements in the nanoscale. This paper presents the latest trends in manufacturing and process automation as well as in metrology. The challenges of the future are discussed and solutions are proposed based on continuous collaboration works.